2013
DOI: 10.1093/infdis/jit574
|View full text |Cite
|
Sign up to set email alerts
|

Human Natural Killer Cells Acting as Phagocytes Against Candida albicans and Mounting an Inflammatory Response That Modulates Neutrophil Antifungal Activity

Abstract: Our results show a unique pattern of NK cell interaction with C. albicans, which involves direct proinflammatory activation and modulation of PMN activity. For the first time, phagocytosis of a pathogen is shown to contribute to NK cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 46 publications
10
95
0
Order By: Relevance
“…52 Additional evidence that cross-talk between these 2 cell types can also occur in vivo has recently been shown in a mouse model of systemic fungal infection, in which an IL-17-NK cell-GM-CSF axis was found to be critical for the modulation of neutrophil fungicidal activity. 53 In line with these findings, in vitro coculture of human NK cells and neutrophils in the presence of Candida albicans resulted in a NK-mediated enhancement of neutrophil antifungal activity, concomitantly with a neutrophilmediated inhibition of NK-cell activation, 54 suggesting that interactions between these 2 cell types might serve to reciprocally modulate their responses.…”
Section: Cross-talk Between Neutrophils and Innate Immune Cellsmentioning
confidence: 60%
“…52 Additional evidence that cross-talk between these 2 cell types can also occur in vivo has recently been shown in a mouse model of systemic fungal infection, in which an IL-17-NK cell-GM-CSF axis was found to be critical for the modulation of neutrophil fungicidal activity. 53 In line with these findings, in vitro coculture of human NK cells and neutrophils in the presence of Candida albicans resulted in a NK-mediated enhancement of neutrophil antifungal activity, concomitantly with a neutrophilmediated inhibition of NK-cell activation, 54 suggesting that interactions between these 2 cell types might serve to reciprocally modulate their responses.…”
Section: Cross-talk Between Neutrophils and Innate Immune Cellsmentioning
confidence: 60%
“…The decrease of the gene expression of perforin with a concomitant increase of the intracellular protein concentration seems surprising, but can be explained by the fact that upon activation with A. fumigatus, NK cells rapidly upregulate the translation of preexisting mRNA of perforin [17]. The presence of A. fumigatus also leads to a slight increase of the perforin levels in the supernatant due to degranulation, an effect which has also been observed in NK cells coincubated with R. oryzae or C. albicans [13,18]. However, as IL-2 prestimulation of NK cells alone already results in relatively high extracellular perforin levels and enhanced cytotoxicity, A. fumigatus only had a marginal effect on the extracellular perforin concentration.…”
Section: Discussionmentioning
confidence: 98%
“…They exhibit not only cytotoxicity against viral infection and bacteria invasion but also anti-tumor effects. 127 Studies have shown the inhibitory effect of NK cells on a variety of fungi including Cryptococcus neoformans, 128 Candida albicans, 129 Aspergillus fumigatus 130 and Rhizopusoryzae. 131 More progress has been made in understanding the function of NK cells in candidiasis.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…137 It is plausible that the synapse leads to a polarization of the receptors on NK cells, followed by degranulation, the release of perforin, granzyme, granulysin or other effector molecules. 129,136,138 Perforin has been proved to play an important role in direct antifungal process. 129 Perforin displays its cytotoxicity by perforating the cell membrane and finally inducing lysis of the target cell.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
See 1 more Smart Citation